African American readings of Paul : reception, resistance, and transformation - Bowens, Lisa M. (Grand Rapids, MI, William B Eerdmans Publishing Company, 2020)
"A historical survey of African American Pauline hermeneutics from the 1700s to the mid-twentieth century"--
Includes bibliographical references (pages 311-325) and index.
Keywords: Bible. -- Criticism, interpretation, etc; African American preaching -- History; African Americans -- Religion -- History